Squat Jump Exercise Increased Spike Jump and Block Jump Reach of Junior Volleyball Athletes - Nasuka, Nasuka; Pradana, Asdi Wahyu (KnE Social Sciences, 2019)
Spike jump and block jump were characteristic movements of volleyball. These movement were determined by explosive power of leg, strength of musculoskeletal, length of lower limb and length of arm. Explosive power could be enhanced by plyometric exercise, like squat jump. The aims of study to analyse the role of squat jump exercise program on spike jump reach and block jump reach of junior volleyball athletes. Twenty-three junior athletes (male 11 and female 12) participated in pre and post-test experiment study. The squat jump exercise program was conducted three time a week, for along 7 weeks. The squat jump exercise involved squat jump, squat jumpwithbox,forearmpassingwhilesquatjumpandsquatjumpwithrunningtakeoff. The data were analysed by paired t-test to compare pre and post-test. The experiment resultedincreasingofspikejumpbothmen(p<0.001)andwomen(p<0.001).Increasing of block jump in men (p<0.001) and women (p=009). We concluded that squat jump exercise regularly effective to increase the spike jump and block jump reach junior volleyball athletes. Keywords: block_jump, squat_jump, spike_jump, volleyball